Automatic control of the step-up transformer tap changer and generator voltage regulator - Hinders, Kim (My University, 2015)
In the modern power systems advanced automation is the first choice for all operations. At the same time when the automation level is advanced, safety and security are also vital. In this thesis automatic voltage control between two active controllers is analysed with all needed safety interlocks and limiters. The switching operations in a grid can result in large voltage fluctuations for which the power plant controllers need to be smoothly designed/adjusted so that there is minimum impact on the power plant equipment and its auxiliaries. The aim of this thesis is to achieve smooth operation between the transformer IED and generator automatic voltage regulator. With the IED it is possible to control voltage level through the transformer tap changer. The generator automatic voltage regulator controls the output voltage level of the generator. The purpose is to respond to grid voltage fluctuations which are caused by reactive load demands. When grid voltage varies the automatic controls should react in a smooth way so that the transformer IED changes tap position automatically to large voltage fluctuations and the generator automatic voltage regulator responds to smaller voltage fluctuations. This action is achieved by setting right parameters to the transformer IED’s automatic voltage control function. The automatic controllers that are going to be used are RET670 transformer IED and generator automatic voltage regulator Unitrol. The thesis includes a theoretical study about generator, step-up transformer and protection systems used in Wärtsilä power plants. The thesis studies also RET670 and Unitrol product manuals. The results are achieved by communication and meetings with power plant system experts, product specialists and information gathered from product manuals. Testing of results are done with Matlab/Simulink Wärtsilä Power plant model. The results show that automatic voltage control is possible. This thesis gives a guideline for a real case power plant project were automatic voltage control is going to be used.
Keywords: Automatic voltage regulator; on-load tap changer; automatic voltage control; fi=Energiatekniikka|en=Energy Technology|; fi=Sähkö- ja energiatekniikan koulutusohjelma (DI)|